Abusive Head Trauma through Shaking: Examination of the Perpetrators According to Dating of the Traumatic Event. (7th June 2021) - Laurent‐Vannier, Anne; Bernard, Jonathan Y.; Chevignard, Mathilde
Abstract : Effective prevention of abusive head trauma (AHT) requires the identification of potential perpetrators. Current evidence suggests that infant shaking, as a mechanism of AHT, produces immediate symptoms, allowing for the dating of the event based on clinical symptoms. Determining precisely when symptoms occurred may help law enforcement to identify the perpetrator. We retrieved written legal statements and medical records from birth to age at diagnosis of 100 infants consecutively diagnosed with AHT through shaking (2011–17), using forensic expertise files. Timing of abuse allowed for the identification of perpetrators in 91 cases. All abusive events occurred inside a home (parent's or nanny's), never outdoors or in a public place, and always in the presence of only one adult. Approximately one‐third ( n  = 32) of the perpetrators were males (31 fathers) and two‐thirds ( n  = 59) were females: 49 of them were the infant's nanny and ten were the infant's mother. Infants were not described as crying habitually. Better knowledge of the context of AHT events and risk situations, including recent implementation of a new or unusual modality of childcare, and being the only adult in a home with an infant, should facilitate prevention, including targeted training and avoidance of situations associated with risk. Key Practitioner Messages: Abusive events occur in the presence of a single adult, within the privacy of a home. First signs of abuse most commonly occur in a recent, therefore unusual, form of childcare. With rare exceptions, the perpetrator is either the nanny or one of the parents. Identification of the perpetrator and better knowledge of the context of abuse should allow improving targeted prevention.